Design and Fabrication of Laminated Composite Tube Using Modified Bladder Assisted Compression Molding Technique - Ganesh Kumar, K.; Jin Ee, Lee; Lau Tze Way, Saijod; Yaakob, Yuhazri; M.H. Megat Ahmad, M.; ., . (International Journal of Engineering and Technology, 2019)
Fiber reinforced composites especially polymer base fiber are finding increasing application due to their high specific strength and stiffness to weight ration.  Several uses of composite material are including marine, aeronautical and piping applications. Even though, they are known for having specific strength and stiffness; lacking or limited fabrication methods specifically for tube shapes is a disadvantage.   In this current paper, a new way of fabricating cylindrical composite tubes using modified bladder assisted compression molding (MBACM) was presented. Glass fiber reinforced composite tubes are fabricated with fiber content in a mat form which consists from 1 to 5 layers. This technique provides capability for producing tube specimens with an internal diameter around 50mm and lengths up to 300mm. The feasibility of this manufacturing method is demonstrated by fabricating laminated composite cylinder using multiple numbers of plies. To evaluate the mechanical properties of the fabricated composite tubes, quasi-static crushing test were conducted to assess crashworthiness and monitor crushing mechanisms corresponding to each layers. This present work confirms that cylindrical composite tube can be fabricated using MBACM technique and the increasing layer of E-glass fiber is significantly changing the mechanical properties to have higher performance in strength.